TO THE FORMATION OF PEDAGOGICAL CULTURE OF THE FUTURE TEACHER - Sydorenko Т. Д.; Ponomarenko Т. В. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the professional-pedagogical of the teacher and degree of their importance for students in formation of their pedagogical culture are considered.